Mímir global product development of an atmospheric water generator - Brännström, Erik; Sundberg, Pontus; Wenngren, Johan; Åhman, Jenny (2009)
Water is the most precious resource known to mankind. Its importance to the survival of life on the planet can hardly be overemphasized. However, lack of access to pure drinking water is one of the key issues facing the world today. Traditional sources such as rivers, lakes and ground water have proved to be highly unreliable sources of drinking water. Therefore, there is a need to develop a novel, innovative technology that is more reliable and is able to produce pure and safe drinking water at all locations even under adverse environmental conditions. With this vision in mind, the design team set on the task to design and develop a new generation atmospheric water generator to harness nature’s most abundant resource: air. The project was founded by the American company Immerse Global and the Swedish PIEp organization. PIEp stands for Product Innovation Engineering program and is a national research program with the purpose of strengthening the ability in innovative product and business development. The design team had a unique setting of members from five different Universities – Helsinki University of Technology (TKK), Luleå University of Technology (LTU), Lund Faculty of Engineering (LTH), Royal Institute of Technology (KTH) and Stanford University (SU). Validerat; 20101217 (root)